INFORMATION SYSTEM DEVELOPMENT FOR WATER TREATMENT TECHNOLOGY IN DISTRICT PANDEGLANG USING OPEN SOURCE SOFTWARE (OSS) - Heru Dwi Wahjono (Jurnal Rekayasa Lingkungan)
Clean water needs in almost all regions in Indonesia became a very important thing nowadays, although the areas not experiencing drought. This is due to existing water is no longer eligible for use as daily life water. In some areas the water have been polluted and certain natural conditions make it difficult for population to get their water. Pandeglang district is one of disadvantaged areas that experiencing problems of clean water needs, although this area has water resources are abundant. To help residents in solving this problem, it will be required an information of water treatment technology that can be widely accessed by residents in the Pandeglang district. By using opensource software applications, the information system for water treatment technology can be developed to provide information of appropriate technology needs for solving the problem of providing clean water in Pandeglang.keywords : information system for technology, clean water management, waste water treatment, environmental technology, hypertext document, free open sourcesoftware (OSS).